Proceedings of the 22nd IEEE International Conference on Application-specific Systems, Architectures, and Processors (ASAP) - Cavallaro, Joseph R.; Ercegovac, Milos D.; Hannig, Frank; Ienne, Paolo; Swartzlander Jr., Earl E.; Tenca, Alexandre F. (Institute of Electrical and Electronics Engineers, 2011)
The proceedings contain 36 papers. The topics discussed include: CusComNet: a customisable network for reconfigurable heterogeneous clusters; address generation scheme for a coarse grain reconfigurable architecture; accelerating vision and navigation applications on a customizable platform; a high-performance, low power linear algebra core; a decimal floating point fused multiply-add unit with a novel decimal leading zero anticipator; longest prefix match and updates in range tries; lowcost hardware profiling of run-time and energy in FPGA embedded processors; TimeTrial: a low-impact performance profiler for streaming data applications; system-level design space exploration for dedicated heterogeneous multiprocessor systems; and decentralized dynamic resource management support for massively parallel processor array
UnivIS-Import:2015-07-08:Pub.2011.tech.IMMD.inform.procee